Digitalization and Sharia Financial Literacy as Strategies for MSME Empowerment in Bekasi Regency - Mohammad Hatta Fahamsyah; Muhammad Najamuddin Dwi Miharja; Adrianna Syariefur Rakhmat; Muhammad Hamdan Ainulyaqin; Gina Nopiyanti (Lentera Pengabdian, 2026)
Micro, Small, and Medium Enterprises play an important role in supporting regional economic development; however, they continue to face challenges related to digital technology adoption and effective financial management. Limited digital literacy and insufficient understanding of sharia-based financial practices often hinder business competitiveness and sustainability. This community service program aimed to enhance the capacity of business owners in utilizing digital technology for marketing activities and implementing sharia-based financial management practices to support sustainable business growth. The program was conducted on June 6, 2026, in Bekasi Regency and involved fifteen micro, small, and medium enterprise owners. The methods employed included socialization, training sessions, hands-on practice, mentoring, and evaluation through pre-activity and post-activity assessments. The training materials covered digital marketing strategies, the use of social media and online marketplaces, digital financial recording, and financial management based on sharia principles. The results demonstrated a significant improvement in participants' understanding of business digitalization and sharia financial management. Participants showed increased ability to utilize digital platforms for marketing, operate digital bookkeeping applications, and manage business finances more systematically. Furthermore, most participants successfully implemented digital marketing practices and financial recording systems in their business operations. The program indicates that the integration of digitalization and sharia-based financial management can effectively improve the capacity, competitiveness, and sustainability of micro, small, and medium enterprises.